(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: Occupational stress among healthcare workers (HCWs) significantly impacts their health and the quality of healthcare services. This study aimed to assess the prevalence and identify factors associated with occupational stress among HCWs at Dong Do Hospital, Hanoi, in 2023. Methodology: We utilized a cross-sectional study design with 245 HCWs participating through the administration of the Job Content Questionnaire (JCQ). Results: The study found that 24% of HCWs experienced significant job stress, with notable variations across different departments. Factors significantly associated with higher levels of stress included high job demands, low job control, and inadequate support from colleagues. Notably, demographic factors such as age and gender did not show a significant relationship with occupational stress levels. Conclusion and recommendation: Based on the findings, we recommend targeted interventions to improve job control, enhance workplace support, and manage job demands to mitigate stress among HCWs. This study contributes to the understanding of occupational stress in a hospital setting and suggests pathways for interventions to enhance worker well-being and healthcare efficiency.